Pedagogical Methods and Conditions for the Innovative Formation of Motivation of Young Handball Players - Khatamov Zafarjon Nazirjonovich (European Science Publishing, 2023)
High achievements in sports are closely related to the motivational field of athletes. Motivation is not only the main feature of the athlete's personality, which leads him to the goal, but also affects the nature of all processes that occur in the body during the activity. Insufficient assessment of the role of motivational factors in working with young athletes, taking into account the dynamics of changes in motives by sports teachers, coaches, athletes often leads to the fact that a person cannot demonstrate his capabilities during sports activities.
Keywords: motive, sports motivation, innovation, Sports Activity, young handball players, personal characteristics, level of claims.